Exchange Rate Exposure and Crude Oil Price: The Case of an Emerging Market - Meenchee Hong,; Ei Yet Chu,; Saw Imm Song, (Asian Academy of Management Journal of Accounting and Finance, 2018)
The purpose of this study is to examine the depreciation of USD and crude oil price on exchange rate exposure in Malaysia. Based on the argument that domestic and foreign markets could affect foreign exchange exposure, the study examined 993 public listed firms that involved in domestic business, foreign sales, and assets, respectively. The sample period of 2014 to 2016 illustrates different time-varying conditions when the depreciation of Ringgit Malaysia and crude oil price were the most severe for the last decades. The findings show that firms with foreign sales face the most significant negative exposure of foreign exchange, followed by domestic firms and firms with foreign assets. The study shows that many Malaysia export firms are not effective in hedging, hence, they did not benefit from the depreciation of Ringgit Malaysia and crude oil price. The study concludes that there is an influence of domestic and foreign market effects on foreign currency exposure in the economy.